Peripheral chemoreflex function in hyperoxia following ventilatory acclimatization to altitude. - Pedersen, M; Robach, P; Richalet, J; Robbins, P (2000)
After a period of ventilatory acclimatization to high altitude (VAH), a degree of hyperventilation persists after relief of the hypoxic stimulus. This is likely, in part, to reflect the altered acid-base status, but it may also arise, in part, from the development during VAH of a component of carotid body (CB) activity that cannot be entirely suppressed by hyperoxia. To test this hypothesis, eight volunteers undergoing a simulated ascent of Mount Everest in a hypobaric chamber were acutely exposed to 30 min of hyperoxia at various stages of acclimatization. For the second 10 min of this exposure, the subjects were given an infusion of the CB inhibitor, dopamine (3 microg. kg(-1). min(-1)). Although there was both a significant rise in ventilation (P < 0.001) and a fall in end-tidal PCO(2) (P < 0.001) with VAH, there was no progressive effect of dopamine infusion on these variables with VAH. These results do not support a role for CB in generating the persistent hyperventilation that remains in hyperoxia after VAH.